On a connection between formulas about q–gamma functions. Issue 3 (2nd July 2016) - Koepf, Wolfram; Rajković, Predrag M.; Marinković, Sladjana D.
Abstract : In this short communication, we want to pay attention to a few wrong formulas which are unfortunately cited and used in a dozen papers afterwards. We prove that the provided relations and asymptotic expansion about the q -gamma function are not correct. This is illustrated by numerous concrete counterexamples. The error came from the wrong assumption about the existence of a parameter which does not depend on anything. Here, we apply a similar procedure and derive a correct formula for the q -gamma function.